Colistin Resistance and Molecular Characterization of the Genomes of mcr-1-Positive Escherichia coli Clinical Isolates - Li, Qiaoling; Qian, Changrui; Zhang, Xueya; Zhu, Tingting; Shi, Weina; Gao, Mengdi; Feng, Chunlin; Xu, Ming; Lin, Hailong; Lin, Li; Lu, Junwan; Lin, Xi; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Research on resistance against polymyxins induced by the mcr-1 gene is gaining interest. In this study, using agar dilution method, polymerase chain reaction, and comparative genomic analysis, we investigated the colistin resistance mechanism of clinical E. coli isolates. The minimum inhibitory concentration (MIC) analysis results revealed that of the 515 isolates tested, bacteria with significantly increased MIC levels against colistin were isolated in 2019. Approximately one-fifth (17.14% to 19.65%) of the isolates showed MIC values ≥1 mg/L against colistin in 2015, 2016, and 2017. However, in 2019, up to three-quarters (74.11%, 146/197) of the isolates showed MIC values ≥1 mg/L against colistin indicating an increase in colistin resistance. Six isolates (EC7518, EC4968, EC3769, EC16, EC117, EC195, 1.13%, 6/515) were found to carry the mcr-1 gene and a novel mcr-1 variant with Met2Ile mutation was identified in EC3769. All six strains showed higher MIC levels (MIC=4 mg/L) than any mcr-1-negative strains(MIC≤2 mg/L). Whole-genome sequencing of the six mcr-1-positive isolates revealed that EC195 carried the highest number of resistance genes (n = 28), nearly a half more than those of the following EC117 (n = 19). Thus, EC195 showed a wider resistance spectrum and higher MIC levels against the antimicrobials tested than the other five isolates. Multi-locus sequence typing demonstrated that these mcr-1-positive strains belonged to six different sequence types. The six mcr-1 genes were located in three different incompatibility group plasmids (IncI2, IncHI2 and IncX4). The genetic context of mcr-1 was related to a sequence derived from Tn6330 (ISApl1-mcr-1-pap2-ISApl1). Investigations into the colistin resistance mechanism and characterization of the molecular background of the mcr genes may help trace the development and spread of colistin resistance in clinical settings.